Flory : a miraculous story of survival - Van Beek, Flory A. (New York : HarperOne, 2008)
Documents the story of a young Jewish girl and her future husband, who fled Nazi-occupied Holland, narrowly survived the sinking of the S.S. Bolivar, and endured many years on the run before finding freedom.
The early years -- Storm clouds rising -- The odyssey of the SS Simon Bolivar -- Holland invaded -- The persecution begins -- The deportations -- The hiding years -- The hiding place -- Fear, our companion -- Working for the resistance -- A night of infamy -- Miracles do happen -- The road to freedom -- The end of the road -- Epilogue.
Keywords: Van Beek, Flory A; Jews -- Netherlands; Holocaust, Jewish -- Netherlands -- 1939-1945; Netherlands